Potret Pendidikan dan Kemiskinan di Indonesia dalam Novel Laskar Pelangi Karya Andre Hirata - Rini Widiastuti (JENTERA: Jurnal Kajian Sastra, 2021)
This paper will examine and reflect on the relationship between literature and education, by addressing the issues surrounding the development of the education system in Indonesia through Andrea Hirata's Laskar Pelangi "glasses". Andrea Hirata shows through the novel Laskar Pelangi that education is not a place where one seeks knowledge, but how to live it. Significantly, the most prominent problem discussed in the novel Laskar Pelangi is the theme of education in Indonesia, and the author is interested in seeing this problem through the realities of the ups and downs of education in Indonesia. As for this purpose, the author analyzes the problems to be highlighted by using the genetic-structuralism method. The use of this method is based on the reason that education like what is contained in the novel Laskar Pelangi is a reflection of the reality of education in Indonesia. And in order to understand the issue more clearly, the analysis of the novel will not only look at the educational issues as contained in the novel (intrinsic), but also in terms of their references to the real world of Indonesian education (extrinsic).AbstrakTulisan ini akan meneliti dan merenungkan hubungan antara sastra dan pendidikan, dengan menjurus kepada persoalan di sekitar perkembangan sistem pendidikan di Indonesia melalui “kacamata” Laskar Pelangi karya Andrea Hirata. Andrea Hirata menunjukkan lewat novel Laskar Pelangi bahwa pendidikan bukanlah tempat seseorang menuntut ilmu, tetapi bagaimana menjalaninya. Secara signifikan, masalah yang paling menonjol yang dibicarakan dalam novel Laskar Pelangi adalah tema pendidikan di Indonesia dan penulis tertarik untuk melihat masalah tersebut melalui persoalan kenyataan pasang-surut pendidikan di Indonesia. Adapun untuk tujuan tersebut, penulis melakukan analisis atas masalah yang hendak disoroti dengan menggunakan metode genetik-strukturalisme. Penggunaan metode ini didasarkan pada alasan bahwa pendidikan seperti apa yang terkandung dalam novel Laskar Pelangi adalah refleksi dari suatu realitas pendidikan di Indonesia. Demi memahami persoalan tersebut lebih jelas, maka analisis terhadap novel tersebut tidak hanya dilakukan untuk melihat persoalan pendidikan tersebut seperti apa yang terdapat dalam novel (intrinsik), tetapi juga dalam hal referensinya ke dunia nyata pendidikan Indonesia (ekstirinsik).